2021
DOI: 10.3390/ijerph18105180
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Impulsiveness, Self-Esteem, Irrational Gambling Belief and Problem Gambling Moderating Effects of Gender

Abstract: The present study investigated the relationship between impulsivity, self-esteem, irrational gambling belief, and problem gambling and also explored whether the relationships between these constructs are different for males and females. Participants included 563 college students with 259 males (46.0%) and 304 females (54.0%) from Korea. Participants completed a survey. The results showed that 5.3% of students were problem gamblers, while 9.4% were moderate-risk gamblers. The relationships between impulsivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
4
0
2
Order By: Relevance
“…Çelik et al determined the probable pathological gambling addiction in university students at the level of 1.2% (Çelik et al, 2022). In their study, Choi and Kim found that 16.3% of the participants were in the low-risk, 9.4% in the medium-risk and 5.4% in the problematic group in terms of problematic gambling behavior (Choi & Kim, 2021). Yokomitsu et al found the rate of probable problem gambling among students to be 5.1%, close to our study (Yokomitsu et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Çelik et al determined the probable pathological gambling addiction in university students at the level of 1.2% (Çelik et al, 2022). In their study, Choi and Kim found that 16.3% of the participants were in the low-risk, 9.4% in the medium-risk and 5.4% in the problematic group in terms of problematic gambling behavior (Choi & Kim, 2021). Yokomitsu et al found the rate of probable problem gambling among students to be 5.1%, close to our study (Yokomitsu et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, Koç and colleagues also found higher SOGS scores in males compared to females (Koç et al, 2023). Choi and Kim similarly found a higher SGOS score in men than in female (Choi & Kim, 2021). Cakici et al found pathological gambling behavior at a higher rate in male students than in females (Çakıcı et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Self-esteem could be defined as a global evaluation of oneself that determines a positive or negative attitude towards the self [ 47 ]. It has been related to high mental health [ 48 ] and, in the field of addiction, it has negative relationships with substance use [ 49 ], gambling disorder [ 50 ], and exercise addiction [ 41 ], as well as technological addictions, such as internet addiction [ 51 ], internet gaming disorder [ 52 ], and problematic smartphone use [ 53 ]. In light of this evidence, the deepening of the protective role of self-esteem on social media addiction appears relevant, by exploring not only the direct associations between these two constructs but also the moderating effects of self-esteem in the relationships between other intervening factors.…”
Section: Introductionmentioning
confidence: 99%
“…Low SE has generally been associated with deleterious outcomes that include, but are not limited to, elevated credit card debt, self-neglect, obesity, hoarding behaviors, chronic eating disorders and gambling addiction (Choi and Kim, 2021; Argo and White, 2012; Pinto et al , 2004). Understandably, consumer researchers have a keen interest in the impact of SE on purchasing behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%